Cardiovascular damage during lupus in black African subjects - NV, Yaméogo; SJ-B, Tougouma; J, Zabsonré; KJ, Kologo; WS, Tiemtoré; LJ, Kagambèga; WPAH, Bagbila; A, Traoré; AK, Samadoulougou; P, Zabsonré (Journal of Cardiology and Cardiovascular Medicine, 2018)
Introduction: Systemic lupus is a disseminated inflammation of the conjunctive tissue. Cardiovascular lesions are the first cause of morbidity and mortality in the course of that disease. These lesions are prevalent in 30 to 62% of cases, depending on whether the diagnostic tool is clinical, echocardiographic, or autopsic. Any part of the heart can be affected, yielding manifestations of pericarditis, endocarditis, coronary heart disease, conduction disorders, and rarely myocarditis. Objective: Describe cardiac manifestations during the follow up of patients diagnosed with systemic lupus. Patients and Methods: We conducted a transversal descriptive study over a period of 27 months, in the departments of Internal Medicine, Dermatology, and Cardiology of Yalgado Ouedraogo University Hospital of Ouagadougou. All patients diagnosed with systemic lupus according to the American College of Rheumatology criteria, and having done an EKG, a Holter EKG, or a transthoracic echocardiography, were included in the study. Data were collected from inpatient medical records, outpatient follow up registry and booklets. Results: Cardiovascular lesions were prevalent in 7 cases (43.75%) out of 16 patients diagnosed with systemic lupus. Mean age of patients was 36 years, with extremes of 23 and 51 years. Only female patients were affected in our study. Cardiac manifestations were mainly benign pericarditis, heart failure, and conduction disorders. Conclusions: Cardiovascular manifestations are frequent during the course of systemic lupus, and occur after few years of disease progression. Transthoracic echocardiography and EKG remain useful non-invasive explorations for the assessment of cardiovascular lesions, despite minor shortcomings.